Effect of crop establishment methods on seed germination, seedling mortality and growth of Bt cotton (Gossypium hirsutum) -based intercropping systems - Rajpoot, Sudhir K.; Rana, D.S.; Choudhary, Anil K. (Annals of Agricultural Research, 2016)
A field experiment was conducted at ICAR-Indian Agricultural Research Institute, New Delhi during the (Kharif) season of 2012 to evaluate the effect of crop establishment methods on seed germination, seedling mortality and growth of Bt cotton (Gossypium hirsutum L.)-based intercropping systems. The results revealed that percent germination and mortality of germinated seedlings and final plant stand/m2 significantly influenced by methods of crop establishment. Germination percentage of cotton seeds was 80.2% under direct sowing which was significantly lower than the germination percentage (97.5 %) recorded under nursery raised for transplanting the cotton crop. Plant height, leaf area index (LAI) and dry matter/plant recorded under direct sowing of cotton were significantly higher than transplanted cotton. However, seed cotton yield/ha was 5.23% higher under transplanted cotton, which might be due to 14-15% higher plant stand under transplanting than direct sown cotton crop.